Industrial democracy and best practice in Thailand: a stakeholder study - Joungtrakul, Jamnean (Curtin University, 2005)
This research investigated the perceptions on industrial democracy of selected stakeholder groups in the Thai industrial relations system. Three research questions were posed. How do the selected stakeholders express their knowledge of industrial democracy? What are the similarities and differences in perceptions of the ‘industrial democracy in practice’ concept held by members of the selected stakeholder groups? What are emergent best practices in industrial democracy? In order to provide some answers to these questions a number of research objectives were developed: To identify knowledge of industrial democracy in Thailand as perceived by selected stakeholders; To investigate the similarities and differences in stakeholder perceptions of industrial democracy; To compare the similarities and differences in stakeholder perceptions of industrial democracy; To identify problems and difficulties encountered from the practicing of industrial democracy within Thai business organizations; To reveal best practice in industrial democracy as expressed by the stakeholders. This research studied employee participation at five levels: board level: employee representation at board level; plant level: employee representation at plant level; shop floor level: employee participation at shop floor level; financial level: employee participation at the financial level; disclosure of information level: employee participation in disclosure of information.This research collected data from the following ten stakeholder groups of the Thai industrial relations system: employees of non-unionized companies: shop floor level; employees of non-unionized companies: supervisory level; trade union leaders: national level; trade union leaders: company level; employers of non-unionized companies; employers organization leader group; government officials; members of tripartite bodies; human resource managers; labour academics. This research focuses on the knowledge and perceptions of stakeholders of the Thai industrial relations system relating to industrial democracy in practices in Thailand. The ontological assumption rests on the basis that realities being constructed by the stakeholders being investigated. These realities are not objective but subjective and that multiple realities exist. This research required the researcher to interact with the stakeholders in the Thai industrial relations system in relation to their knowledge and perception of industrial democracy in practice in Thailand. The epistemology of this research was subjectivist, the knower and respondent co-creating understanding. A grounded theory approach was taken. The centrepiece is the development or generation of a theory closely related to the context of the phenomena being studied. The idea is to discover theory in a systematic yet emergent way. Grounded theory is closely associated with two research traditions, produced in outline below.These are phenomenology and symbolic interactionism. The findings are presented in a model identifying nine common characteristics enhancing the best practice of industrial democracy. The model is proposed as a tentative Thai industrial democracy model. The nine components of the model include: constructive employer and employee or trade union relationships; determination of forms and process of participation; forms and practices of participation; upholding common goals and sharing both success and failures; implementation and change management; pro-active and promotional government roles; Thai cultures and Buddhist philosophy and principles; laws as a frame of reference; learning and practicing together continually. Eight sets of Buddhist philosophy and principles are integrated into the Thai industrial democracy model. They are: the six directions; the divine abiding; the principles for helpful integration; the principles of success; the ten regal qualities; the qualities of a good or genuine person; the principles of collective responsibility; and the principles for conducting oneself as a good citizen. Seven concepts of Thai culture are also integrated in the Thai industrial democracy model. They are: the concept of helping each other; the concept of Bunkhun; the concept of Kreng Jai; the concept of face saving; the concept of criticism avoidance; the concept of sympathy; and the concept of compromising.